CAUSES OF CANCER IN THE MODERN WORLD (Journal of Universal Science Research, 2024)
The existence of cancer has been known for thousands of years, yet its rates continue to grow despite advances in medicine and human development indexes. In fact, over 35 million new cancer cases are predicted in 2050, a 77% increase from the estimated 20 million cases in 2022. This article will try to highlight key factors in cancer growth and its preventive measures